Method for preparing fluorine-doped tin oxide transparent conductive film through ultrasonic atomization and application of fluorine-doped tin oxide transparent conductive film
By using a combined spray solution of fluorine-containing dopant and lithium hydroxide in ultrasonic spray pyrolysis method, combined with closed spraying environment and iodine tungsten lamp heating, the microscopic defects and resistance stability of the FTO film are solved, and the low Cost, high stability film preparation, suitable for high-end infrared heating equipment.
Patent Information
- Application Number
- CN202411256122.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing ultrasonic spray pyrolysis method for preparing fluorine-doped tin oxide transparent conductive films has problems such as many microscopic defects in the film layer, large specific surface area, high film production cost and poor stability of static resistance, which is difficult to meet the needs of high-end portable electric heating films.
Using a combined spray liquid with fluorine-containing dopant and lithium hydroxide, the pH value of the spray liquid is above 2.0, combined with closed spraying environment and radiated heating of iodine tungsten lamps, it can achieve rapid heating and precise temperature control, reduce film defects and Resistance instability.
FTO films with few microscopic defects, small specific surface area, low square resistance and stable static resistance were prepared. They are suitable for high-end portable infrared heating equipment, reducing production costs and improving the stability of the film.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of functional oxide film preparation, and in particular to a method for preparing a fluorine-doped tin oxide transparent conductive film by ultrasonic atomization and its application. Background Art
[0002] Fluorine-doped tin oxide transparent conductive film (FTO) is a wide bandgap, heavily doped semiconductor material. Its high infrared emissivity and electrothermal conversion efficiency, low resistivity and low preparation cost, as well as the absence of heavy metal elements, make it very suitable as an electric heating film for use in the field of small food infrared heating equipment / utensils. At present, the preparation of thin films mainly relies on vacuum coating technology. The disadvantages of this technology are that the equipment structure is complex, expensive, and the process is cumbersome. The lack of high-quality FTO target materials leads to low photoelectric performance of FTO films prepared by vacuum coating. Compared with traditional vacuum coating technology, ultrasonic spray pyrolysis has the advantages of simple process, low cost, and adjustable stoichiometric ratio of doping elements, and has attracted widespread attention.
[0003] However, the ultrasonic spray pyrolysis equipment developed today is mainly an open spray environment. The substrate temperature is significantly reduced during spray coating, and there are a large number of nano-scale defects on the surface of the prepared film due to the low film forming temperature. These defects continuously absorb oxygen and water vapor in the air, causing the number of oxygen vacancies in the film to change, and the static resistance stability of the material is not high. Secondly, the diffusion of impurity elements from the substrate into the film reduces the conductivity of the film.
[0004] Therefore, developing new FTO film industrial preparation technology to solve the problems of FTO transparent conductive film with many microscopic defects, large specific surface area, and high film production cost is the guarantee for obtaining large-scale, low-square-resistance and stable static resistance films, and is also the key to promoting it to the high-end portable electric heating film market. Summary of the invention
[0005] Based on this, it is necessary to provide a method for preparing fluorine-doped tin oxide transparent conductive film by ultrasonic atomization and its application which can reduce the microscopic defects of the film layer.
[0006] In a first aspect, the present application provides a fluorine-doped tin oxide transparent conductive film spraying liquid, comprising the following components: a tin source, an alcohol, a fluorine-containing dopant and lithium hydroxide, wherein the pH of the spraying liquid is above 2.0.
[0007] In one embodiment, the tin source is at least one of SnCl4·5H2O or SnCl2·2H2O or SnCl4·5H2O and SnCl2·2H2O;
[0008] In one embodiment, the fluorine-containing dopant is trifluoroacetic acid or ammonium fluoride, preferably trifluoroacetic acid.
[0009] In one embodiment, the alcohol is at least one of methanol and ethanol;
[0010] In one embodiment, the pH of the spraying liquid is above 3.0.
[0011] In one embodiment, the molar ratio of the tin source, the fluorine-containing dopant and the lithium hydroxide is 1: "0.45-0.85": "0.05-0.2".
[0012] In one embodiment, the spraying liquid includes a tin source, methanol, trifluoroacetic acid, lithium hydroxide, and ethanol, wherein the mass volume ratio of the tin source, methanol, trifluoroacetic acid, lithium hydroxide, and ethanol is: 1 (g): 6-12 (ml): 0.1-0.3 (g): 0.0001-0.01 (g): 6-12 (ml).
[0013] And / or, the molar ratio of tin source: methanol: trifluoroacetic acid: lithium hydroxide: ethanol is 1: "55-95": "0.45-0.85": "0.05-0.2": "30-70".
[0014] In one of the embodiments, the preparation method of the spray liquid is as follows: a tin source is dissolved in methanol, and trifluoroacetic acid and lithium hydroxide are added, the obtained mixed solution is placed in a high-pressure reactor for reaction, the reaction temperature is set to 65-70°C, the reaction pressure is 0.1-0.3MPa, the reaction time is 1 hour, and after the solution after the reaction is cooled to room temperature, it is taken out and dried at 70°C to obtain a yellow-green powder; the yellow-green powder is dissolved in ethanol to obtain the spray liquid.
[0015] In a second aspect, the present application provides a method for preparing a fluorine-doped tin oxide transparent conductive film by ultrasonic atomization, wherein the fluorine-doped tin oxide transparent conductive film is prepared by ultrasonic atomization of the spray liquid as described in any of the above embodiments.
[0016] In one embodiment, the method comprises the following steps:
[0017] providing the spraying liquid;
[0018] heating the substrate surface;
[0019] The spraying liquid is ultrasonically atomized and sprayed and deposited on the surface of the substrate to prepare the fluorine-doped tin oxide transparent conductive film.
[0020] In one embodiment, the substrate surface temperature is heated to 380-420°C.
[0021] In one embodiment, the substrate is glass or quartz.
[0022] and / or, using an iodine tungsten lamp to radiate and heat the surface of the substrate;
[0023] And / or, when the spraying liquid is ultrasonically atomized and spray-deposited on the surface of the substrate, the deposition environment is closed.
[0024] And / or, when the substrate is spray-deposited, the substrate is placed at an inclination angle ranging from 40° to 50°, the carrier gas is 99.99% pure nitrogen, and the carrier gas flow rate is controlled at 6 to 8 mL / min; the liquid at the bottom of the bottle in the spray chamber is a saturated sodium chloride solution, and the liquid column height is maintained at 20 to 25 cm.
[0025] In one embodiment, the spraying ultrasonic atomization has a mist output of 4800±500mL / h and a thin film deposition time of 5 to 10min;
[0026] And / or, the film thickness of the fluorine-doped tin oxide transparent conductive film is 600-800 nm;
[0027] And / or, the square resistance of the fluorine-doped tin oxide transparent conductive film is 4.4-8.0Ω / □;
[0028] And / or, the grain size of the fluorine-doped tin oxide transparent conductive film is 70±5 nm;
[0029] And / or, the surface roughness RMS of the fluorine-doped tin oxide transparent conductive film is 5.5-6.2 nm.
[0030] In a third aspect, the present application provides an infrared heating device having a substrate and a fluorine-doped tin oxide transparent conductive film prepared on the surface of the substrate, wherein the fluorine-doped tin oxide transparent conductive film is prepared by the method described in any of the above embodiments.
[0031] The above-mentioned fluorine-doped tin oxide transparent conductive film spraying liquid includes the following components: tin source, alcohol, fluorine-containing dopant and lithium hydroxide. The pH of the spraying liquid is above 2.0, and the acidity is relatively low compared to the traditional one. The applicant has found through research that the raw materials for the production of droplets from the traditional spraying liquid are mostly aqueous solutions or organic solutions prepared with SnCl4 and SnCl2. During the preparation process, a large amount of HCl will be generated due to nucleophilic substitution reaction, resulting in excessive acidity of the prepared solution, and the pH value is often below 1.0; the higher acidity of the droplets will increase the microscopic defects of the prepared film layer, and the surface roughness of the film will increase, which will increase the adsorption of gas by the film layer and seriously affect the stability of the film resistance. In this application, the applicant introduces lithium hydroxide and makes the pH of the spraying liquid above 2.0, which is relatively lower than the traditional acidity. This can avoid the problem that "the aqueous solution or organic solution prepared by SnCl4 and SnCl2 will generate a large amount of HCl due to nucleophilic substitution reaction during the preparation process, resulting in excessive acidity of the prepared solution, and the pH value is often below 1.0; the high acidity of the droplets will increase the microscopic defects of the prepared film layer, and the surface roughness of the film will increase, which will increase the amount of gas adsorbed by the film layer and seriously affect the stability of the film resistance." It can improve the microscopic defects of the film layer, reduce the surface roughness of the film, reduce nano-scale protrusions or pits, reduce the amount of gas adsorbed by the film layer, and improve the stability of the film resistance. Moreover, this application innovatively uses a combination of fluorine-containing dopants and lithium hydroxide, which has reduced and controllable acidity, controllable film thickness, and high fluorine doping level, which can better solve the corrosion problems of film growth and coating equipment, and provide conditions for the preparation of high-quality FTO films. The fluorine-containing dopant of the present application may include but is not limited to trifluoroacetic acid or ammonium fluoride, preferably trifluoroacetic acid. The applicant has found through research that trifluoroacetic acid has a better effect than ammonium fluoride.
[0032] The present invention provides a method for preparing an FTO film with few microscopic defects, small specific surface area and low film making cost; based on the improvement of conventional ultrasonic spray equipment, the environment of film deposition is changed from open to closed, the substrate heating method is iodine tungsten lamp radiation heating, and a device with controllable aerosol pressure in the spray chamber is added to realize the control of key process parameters such as heating rate, aerosol pressure in the closed chamber and substrate temperature drop, so as to further achieve the following effects on the basis of conventional ultrasonic spray film making: ① rapid heating (heating rate up to 100°C / s), ② stable temperature field during film coating, and ③ controllable growth of the film layer. Through rapid heating, the attachment of impurity particles on the surface of the substrate and the diffusion of impurity elements of the substrate to the film are reduced, so as to achieve the purpose of reducing film defects; the closed space design reduces the influence of the substrate temperature on the spray droplets and airflow to the minimum, and at the same time, the accuracy of the combined temperature control meets the requirements of stable temperature field of film preparation, and effectively reduces the internal stress of the film layer; the tail pressure design of the spray chamber, in conjunction with the gas pressure regulation at the carrier gas source end, can effectively control a series of physical changes, thermal decomposition reactions and crystallization nucleation processes occurring during the flight of the droplets in the spray chamber, so as to achieve the purpose of controlling the growth of the film. At the same time, the present application adopts a new acidity control technology to obtain a FTO spray liquid with low acidity (pH value greater than 2.0) and high fluorine doping level, solves the corrosion problems of film growth and coating equipment, and provides conditions for the preparation of high-quality FTO films. The present invention can prepare an FTO film with few microscopic defects, small specific surface area, low film square resistance, and small static resistance change rate of the film layer. The film thickness is controlled at 600-800nm. There are no defects such as cracks, second-phase impurity particles, abnormal protrusions and pits on the surface and inside of the film. The film grains grow densely and uniformly, basically maintaining at 70±5nm. The surface of the FTO film is smooth and flat, with a small surface roughness (RMS of the surface root mean square roughness is 5.5-6.2nm, 5μm×5μm range), and the lowest square resistance can reach 4.4Ω / □. It can be used as a semiconductor electric heating film and applied to high-end products such as small infrared heating tubes and plates with low power consumption. DETAILED DESCRIPTION
[0033] In order to facilitate the understanding of the present application, in order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth so as to fully understand the present application, and the preferred implementation methods of the present application are given. However, the present application can be implemented in many different forms and is not limited to the implementation methods described herein. On the contrary, the purpose of providing these implementation methods is to make the disclosure of the present application more thoroughly and comprehensively understood. The present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art belonging to the technical field of the present application. The terms used herein are only for the purpose of describing specific implementation methods and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0034] In a first aspect, the present application provides a fluorine-doped tin oxide transparent conductive film spraying liquid, comprising the following components: a tin source, an alcohol, a fluorine-containing dopant and lithium hydroxide, wherein the pH of the spraying liquid is above 2.0.
[0035] The above-mentioned fluorine-doped tin oxide transparent conductive film spraying liquid includes the following components: tin source, alcohol, fluorine-containing dopant and lithium hydroxide. The pH of the spraying liquid is above 2.0, and the acidity is relatively low compared to the traditional one. It can avoid the problem that "the aqueous solution or organic solution prepared by SnCl4 and SnCl2 will generate a large amount of HCl due to nucleophilic substitution reaction during the preparation process, resulting in excessive acidity of the prepared solution, and the pH value is often below 1.0; the high acidity of the droplets will increase the microscopic defects of the prepared film layer, and the surface roughness of the film will increase, which will increase the amount of gas adsorbed by the film layer, and seriously affect the stability of the film resistance". It can improve the microscopic defects of the film layer, reduce the surface roughness of the film, reduce the amount of gas adsorbed by the film layer, and improve the stability of the film resistance. Moreover, the present application innovatively adopts a combination of fluorine-containing dopants such as trifluoroacetic acid and lithium hydroxide, which has reduced and controllable acidity, and controllable film thickness, high fluorine doping level, can better solve the corrosion problems of film growth and coating equipment, and provide conditions for the preparation of high-quality FTO films.
[0036] In one embodiment, the tin source is SnCl4·5H2O or SnCl2·2H2O or at least one of SnCl4·5H2O and SnCl2·2H2O; for example, the alcohol is at least one of methanol and ethanol; preferably, the alcohol is methanol and ethanol, so that by using methanol and ethanol, the tin source can be dissolved by methanol, and the spray liquid is subsequently prepared by ethanol to improve the ultrasonic atomization effect.
[0037] In one embodiment, the pH of the spraying liquid is above 3.0. Thus, by further reducing the acidity of the spraying liquid, the microscopic defects of the film layer can be further improved, the surface roughness of the film can be reduced, the amount of gas adsorbed by the film layer can be reduced, and the stability of the film resistance can be improved.
[0038] In one embodiment, the molar ratio of the tin source, the fluorine-containing dopant and the lithium hydroxide is 1: "0.45-0.85": "0.05-0.2". The applicant has found that the use of the above molar ratio of the tin source, the fluorine-containing dopant and the lithium hydroxide can further improve the microscopic defects of the film layer, reduce the surface roughness of the film, reduce the amount of gas adsorbed by the film layer, and improve the stability of the film resistance.
[0039] In one embodiment, the spraying liquid includes a tin source, methanol, trifluoroacetic acid, lithium hydroxide, and ethanol, wherein the molar ratio of tin source: methanol: trifluoroacetic acid: lithium hydroxide: ethanol is 1: "55-95": "0.45-0.85": "0.05-0.2": "30-70". For example, the mass volume ratio of tin source, methanol, trifluoroacetic acid, lithium hydroxide, and ethanol is: 1 (g): 6-12 (ml): 0.1-0.3 (g): 0.0001-0.01 (g): 6-12 (ml). In this way, the spraying liquid of each component in the above mass ratio can further improve the microscopic defects of the film layer, reduce the surface roughness of the film, reduce the adsorption of gas by the film layer, and improve the stability of the film resistance.
[0040] In one embodiment, the preparation method of the spraying liquid is as follows: dissolve the tin source in methanol, add trifluoroacetic acid and lithium hydroxide, place the obtained mixed solution in a high-pressure reactor for reaction, set the reaction temperature to 65-70°C, the reaction pressure to 0.1-0.3MPa, and the reaction time to 1 hour. After the solution after the reaction is cooled to room temperature, take it out and dry it at 70°C to obtain a yellow-green powder; dissolve the yellow-green powder in ethanol to obtain the spraying liquid. For example, a FTO spraying liquid with a pH value greater than 2.0 is prepared according to the molar ratio of tin source: industrial methanol: trifluoroacetic acid: LiOH: industrial ethanol = 1: (60-80): 0.5: 0.01: (40-55). Specifically, SnCl4·5H2O or SnCl2·2H2O or a mixture of SnCl4·5H2O and SnCl2·2H2O in any proportion is dissolved in industrial methanol, and a certain amount of trifluoroacetic acid solution and LiOH are added thereto. After that, the obtained mixed solution was placed in a high-pressure reactor for reaction. The reaction temperature was set to 65-70°C, the reaction pressure was 0.1-0.3MPa, and the reaction time was 1 hour. After the solution after the reaction was cooled to room temperature, it was taken out and dried at 70°C to obtain a yellow-green powder. These powders were dissolved in a certain amount of industrial ethanol to obtain a light yellow low-acid FTO spray liquid.
[0041] In a second aspect, the present application provides a method for preparing a fluorine-doped tin oxide transparent conductive film by ultrasonic atomization, wherein the fluorine-doped tin oxide transparent conductive film is prepared by ultrasonic atomization of the spray liquid as described in any of the above embodiments. In this way, the spray liquid of the components provided by the present application is prepared by ultrasonic atomization deposition, which can better improve the microscopic defects of the film layer, reduce the surface roughness of the film, reduce the amount of gas adsorbed by the film layer, and improve the stability of the film resistance.
[0042] In one embodiment, the method comprises the following steps:
[0043] providing the spraying liquid;
[0044] heating the substrate surface;
[0045] The spraying liquid is ultrasonically atomized and sprayed and deposited on the surface of the substrate to prepare the fluorine-doped tin oxide transparent conductive film.
[0046] In one embodiment, the surface temperature of the substrate is heated to 380-420°C. For example, the substrate is glass or quartz. For example, an iodine tungsten lamp is used to radiate and heat the surface of the substrate; in this way, the heating rate can be improved, and the heating rate can be up to 100°C / , which can better ensure the temperature field during coating and improve the coating effect.
[0047] In one embodiment, when the spray liquid is ultrasonically atomized and sprayed onto the substrate surface, the deposition environment is closed. Thus, the present application achieves precise control of key process parameters such as heating rate, closed chamber aerosol pressure, and substrate temperature drop by changing the deposition environment from the traditional open to a closed one, combining iodine tungsten lamp radiation heating, and adding a device for controlling the aerosol pressure in the spray chamber, thereby improving the control effect.
[0048] In one embodiment, when the substrate is sprayed and deposited, the substrate is placed at an angle of 40° to 50°, the carrier gas is 99.99% pure nitrogen, and the carrier gas flow rate is controlled at 6 to 8 mL / min; the bottom liquid of the spray chamber uses a saturated sodium chloride solution, and the height of the liquid column is maintained at 20 to 25 cm. In this way, the coating effect can be improved, and the microscopic defects of the film layer can be further improved, the surface roughness of the film can be reduced, the amount of gas adsorbed by the film layer can be reduced, and the stability of the film resistance can be improved.
[0049] In one of the embodiments, the spraying ultrasonic atomization has a mist output of 4800±500mL / h, and the film deposition time is 5 to 10min; for example, the film thickness of the fluorine-doped tin oxide transparent conductive film is 600 to 800nm; for example, the square resistance of the fluorine-doped tin oxide transparent conductive film is 4.4 to 8.0Ω / □; the square resistance is the film surface resistance, and the unit is Ω / □, which refers to the film resistance within a plane. For example, the grain size of the fluorine-doped tin oxide transparent conductive film is 70±5nm; for example, the surface roughness RMS of the fluorine-doped tin oxide transparent conductive film is 5.5 to 6.2nm. In this way, the coating effect can be improved, and the microscopic defects of the film layer can be further improved, the surface roughness of the film can be reduced, the adsorption of gas by the film layer can be reduced, and the stability of the film resistance can be improved.
[0050] The present invention provides a method for preparing an FTO film with few microscopic defects, small specific surface area and low film making cost; based on the improvement of conventional ultrasonic spray equipment, the environment of film deposition is changed from open to closed, the substrate heating method is iodine tungsten lamp radiation heating, and a device with controllable aerosol pressure in the spray chamber is added to realize the control of key process parameters such as heating rate, aerosol pressure in the closed chamber and substrate temperature drop, so as to further achieve the following effects on the basis of conventional ultrasonic spray film making: ① rapid heating (heating rate up to 100°C / s), ② stable temperature field during film coating, and ③ controllable growth of the film layer. Through rapid heating, the attachment of impurity particles on the surface of the substrate and the diffusion of impurity elements of the substrate to the film are reduced, so as to achieve the purpose of reducing film defects; the closed space design reduces the influence of the substrate temperature on the spray droplets and airflow to the minimum, and at the same time, the accuracy of the combined temperature control meets the requirements of stable temperature field of film preparation, and effectively reduces the internal stress of the film layer; the tail pressure design of the spray chamber, in conjunction with the gas pressure regulation at the carrier gas source end, can effectively control a series of physical changes, thermal decomposition reactions and crystallization nucleation processes occurring during the flight of the droplets in the spray chamber, so as to achieve the purpose of controlling the growth of the film. At the same time, the present application adopts a new acidity control technology to obtain a FTO spray liquid with low acidity (pH value greater than 2.0) and high fluorine doping level, solves the corrosion problems of film growth and coating equipment, and provides conditions for the preparation of high-quality FTO films. The present invention can prepare an FTO film with few microscopic defects, small specific surface area, low film square resistance, and small static resistance change rate of the film layer. The film thickness is controlled at 600-800nm. There are no defects such as cracks, second-phase impurity particles, abnormal protrusions and pits on the surface and inside of the film. The film grains grow densely and uniformly, basically maintaining at 70±5nm. The surface of the FTO film is smooth and flat, with a small surface roughness (RMS of the surface root mean square roughness is 5.5-6.2nm, 5μm×5μm range), and the lowest square resistance can reach 4.4Ω / □. It can be used as a semiconductor electric heating film and applied to high-end products such as small infrared heating tubes and plates with low power consumption.
[0051] In one embodiment, the method for preparing a fluorine-doped tin oxide transparent conductive film by ultrasonic atomization comprises the following specific steps:
[0052] Step 1, prepare a FTO spray liquid with a pH value higher than 3.0. Specifically, SnCl4·5H2O or SnCl2·2H2O or a mixture of SnCl4·5H2O and SnCl2·2H2O in any proportion is dissolved in industrial methanol, and a certain amount of trifluoroacetic acid solution and LiOH are added thereto. Afterwards, the obtained mixed solution is placed in a high-pressure reactor for reaction. The reaction temperature is set to 65-70°C, the reaction pressure is 0.1-0.3MPa, and the reaction time is 1 hour. After the solution after the reaction is cooled to room temperature, it is taken out and dried at 70°C to obtain a yellow-green powder. Dissolve these powders in a certain amount of industrial ethanol to obtain a light yellow low-acid FTO spray liquid.
[0053] Step 2: Place the cleaned glass / quartz substrate into the spray chamber at a certain angle. Then add a certain amount of FTO spray liquid into the ultrasonic sprayer. Subsequently, introduce a carrier gas with a certain flow rate into the coating chamber. The tail end of the equipment is connected by a hose, and the carrier gas introduced into the coating chamber is introduced into the bottom of a liquid bottle with a certain concentration. By adjusting the height of the liquid column, the gas pressure in the coating chamber is regulated.
[0054] Step 3, start the iodine tungsten lamp to radiate heat to the substrate. After 7 to 8 seconds, the substrate temperature reaches 380 to 420°C and is maintained for 30 seconds. Then turn on the ultrasonic atomization plate to bring the cavitated spray liquid droplets into the spray chamber by the carrier gas and deposit them on the hot substrate surface. Maintain a certain spray time to obtain an FTO film on the surface of the glass / quartz substrate;
[0055] Step 4: After the coating is completed, turn off the spray system and the heating system, wait for the sample to cool to room temperature with the furnace, take out the sample, and you can get the FTO film with the required performance.
[0056] In one embodiment, the molar ratio of tin source: methanol: trifluoroacetic acid: lithium hydroxide: ethanol is 1: "55-95": "0.45-0.85": "0.05-0.2": "30-70".
[0057] In one embodiment, in step 2, the substrate is placed at an inclination angle ranging from 40° to 50°. The carrier gas is 99.99% pure nitrogen, and the carrier gas flow rate is controlled at 6 to 8 mL / min. The liquid at the bottom of the bottle is a saturated sodium chloride solution, and the height of the liquid column is maintained at 20 to 25 cm.
[0058] In one embodiment, in step 3, the ultrasonic atomization plate power is 165W, the mist output is controlled at 4800±500mL / h, and the film deposition time is 5 to 10min. During the coating, the substrate temperature drop is controlled at ±1°C.
[0059] In one embodiment, in step 4, the performance indicators of the prepared FTO film show the following characteristics: the film thickness is controlled at 600-800nm, the square resistance is 4.4-8.0Ω / □, the grain size is controlled at 70±5nm, and the surface roughness RMS is 5.5-6.2nm. This film is placed at room temperature and normal conditions (June, July, and August) for 3 months, and the square resistance change rate is less than 2%.
[0060] This has the following beneficial effects:
[0061] (1) The present invention can prepare a FTO electric heating film suitable for high-end portable infrared heating equipment / devices. The sheet resistance of the film is very low, which can be as low as 4.4Ω / □, but it can maintain a high resistance stability. When the sample is placed in the air, the sheet resistance hardly changes.
[0062] (2) The present invention combines ultrasonic spraying with rapid thermal treatment technology, which greatly avoids the adsorption of impurity particles on the surface of the substrate and the diffusion of substrate elements into the film, and effectively reduces point defects in the film.
[0063] (3) The present invention adopts a nearly closed spray chamber, combined with a gentle spray environment, to effectively control the temperature drop of the substrate, allowing the film to grow in a balanced and stable environment, reducing the uneven island growth that causes a large number of protrusions, pits and other defects in the film, thereby effectively reducing the gas adsorption of the finished film and stabilizing the film resistance.
[0064] (4) The present invention controls the pressure of the gas-liquid mixture in the coating chamber by adjusting the composition and height of the tail liquid column, thereby effectively controlling a series of physical and chemical changes that occur when the droplets fly toward the substrate, thereby obtaining a thin film with few defects and a dense structure, and improving the stability of the film layer resistance.
[0065] (5) Low-acid FTO spray liquid reduces corrosion on the membrane surface and corrosion of the acidic liquid on the equipment during the membrane making process. The preparation technology of low-acid solution (especially the addition of excessive industrial methanol, which enhances the reaction degree of solute and solvent near the boiling point of the solvent; and a small amount of LiOH as a guide agent, which further promotes the reaction of solute and solvent and effectively reduces the acidity of the final product) provides a guarantee for the acquisition of high-quality spray liquid.
[0066] (6) The ultrasonic spray technology adopted in the present invention greatly reduces the production cost and is suitable for large-scale industrial production needs.
[0067] In a third aspect, the present application provides an infrared heating device having a substrate and a fluorine-doped tin oxide transparent conductive film prepared on the surface of the substrate, wherein the fluorine-doped tin oxide transparent conductive film is prepared by the method described in any of the above embodiments.
[0068] The infrared heating device provided in the present application is prepared based on the coating method of the present application, has simple process and low cost, and can better improve the micro defects of the film layer, and the film layer has good stability, and the three-month square resistance change rate is less than 2%.
[0069] The present application will be further described below in conjunction with specific embodiments.
[0070] Example 1
[0071] A method for preparing a fluorine-doped tin oxide film by ultrasonic atomization, the specific steps are as follows:
[0072] ①Prepare the spraying liquid: Dissolve 144.33g of SnCl4·5H2O in 1000mL of industrial methanol, and add 23.47g of trifluoroacetic acid solution and 0.10g of LiOH thereto. Afterwards, place the obtained mixed solution in a high pressure reactor for reaction. The reaction temperature is set to 65°C, the reaction pressure is 0.1MPa, and the reaction time is 1 hour. After the solution after the reaction is cooled to room temperature, take it out and dry it at 70°C to obtain a yellow-green powder. Dissolve these powders in 957mL of industrial ethanol to obtain a light yellow low-acid FTO spraying liquid. In this embodiment, the molar ratio of tin source: methanol: trifluoroacetic acid: lithium hydroxide: ethanol is 1:59.77:0.5:0.01:39.96.
[0073] ②Preparation of thin film: Place the cleaned glass / quartz substrate in the spray chamber at 45°. Then add a certain amount of FTO spray liquid into the ultrasonic sprayer. Subsequently, nitrogen with a purity of 99.99% is introduced into the coating chamber, and the gas flow rate is controlled at 7mL / min. The carrier gas introduced into the coating chamber is introduced into the bottom of the bottle of sodium chloride solution with a concentration of 5.4mol / L. The liquid column height is 25cm, and the gas pressure in the coating chamber is regulated; start the iodine tungsten lamp to radiate heat to the substrate. After 8s, the substrate temperature reaches 400℃ and maintains for 30s. Then turn on the ultrasonic atomization plate, and the cavitated spray liquid droplets are brought into the spray chamber by the carrier gas and deposited on the hot substrate surface. Control the spray time to 10min, and the FTO film can be obtained on the surface of the glass / quartz substrate.
[0074] The performance indicators of the obtained FTO film show the following characteristics: film thickness 796nm, square resistance value 4.4Ω / □, grain size controlled at 73nm, surface roughness RMS 6.2nm. After being placed at room temperature for 3 months, the square resistance change rate is 1.9%.
[0075] Example 2
[0076] A method for preparing a fluorine-doped tin oxide film by ultrasonic atomization, the specific steps are as follows:
[0077] ①Prepare the spraying liquid: Dissolve 108.25g of SnCl4·5H2O in 1000mL of industrial methanol, and add 17.60g of trifluoroacetic acid solution and 0.07g of LiOH thereto. Afterwards, place the obtained mixed solution in an autoclave for reaction. The reaction temperature is set to 70°C, the reaction pressure is 0.3MPa, and the reaction time is 1 hour. After the solution after the reaction is cooled to room temperature, take it out and dry it at 70°C to obtain a yellow-green powder. Dissolve these powders in 987mL of industrial ethanol to obtain a light yellow low-acid FTO spraying liquid. In this embodiment, the molar ratio of tin source: methanol: trifluoroacetic acid: lithium hydroxide: ethanol is 1:79.69:0.5:0.01:54.95.
[0078] ②Preparation of thin film: Place the cleaned glass / quartz substrate in the spray chamber at 40°. Then add a certain amount of FTO spray liquid into the ultrasonic sprayer. Subsequently, nitrogen with a purity of 99.99% is introduced into the coating chamber, and the gas flow rate is controlled at 8mL / min. The carrier gas introduced into the coating chamber is introduced into the bottom of the bottle of sodium chloride solution with a concentration of 5.4mol / L. The liquid column height is 20cm, and the gas pressure in the coating chamber is regulated; start the iodine tungsten lamp to radiate heat to the substrate. After 7s, the substrate temperature reaches 380℃ and maintains for 30s. Then turn on the ultrasonic atomization plate, and the cavitated spray liquid droplets are brought into the spray chamber by the carrier gas and deposited on the hot substrate surface. Control the spray time to 5min, and the FTO film can be obtained on the surface of the glass / quartz substrate.
[0079] The performance indicators of the obtained FTO film show the following characteristics: film thickness 600nm, square resistance value 7.6Ω / □, grain size controlled at 71nm, surface roughness RMS 5.9nm. After being placed at room temperature for 3 months, the square resistance change rate is 0.6%.
[0080] Example 3
[0081] A method for preparing a fluorine-doped tin oxide film by ultrasonic atomization, the specific steps are as follows:
[0082] ①Prepare the spraying liquid: Dissolve 123.71g of SnCl4·5H2O in 1000mL of industrial methanol, and add 20.12g of trifluoroacetic acid solution and 0.08g of LiOH thereto. Afterwards, place the obtained mixed solution in a high pressure reactor for reaction. The reaction temperature is set to 67°C, the reaction pressure is 0.2MPa, and the reaction time is 1 hour. After the solution after the reaction is cooled to room temperature, take it out and dry it at 70°C to obtain a yellow-green powder. Dissolve these powders in 1000mL of industrial ethanol to obtain a light yellow low-acid FTO spraying liquid. In this embodiment, the molar ratio of tin source: methanol: trifluoroacetic acid: lithium hydroxide: ethanol is 1.00:69.73:0.5:0.01:48.72.
[0083] ②Preparation of thin film: Place the cleaned glass / quartz substrate into the spray chamber at 50°. Then add a certain amount of FTO spray liquid into the ultrasonic sprayer. Subsequently, nitrogen with a purity of 99.99% is introduced into the coating chamber, and the gas flow rate is controlled at 7.8mL / min. The carrier gas introduced into the coating chamber is introduced into the bottom of the bottle of sodium chloride solution with a concentration of 5.4mol / L. The liquid column height is 25cm, and the gas pressure in the coating chamber is regulated; start the iodine tungsten lamp to radiate heat to the substrate. After 8s, the substrate temperature reaches 400℃ and maintains for 30s. Then turn on the ultrasonic atomization plate, and the cavitated spray liquid droplets are brought into the spray chamber by the carrier gas and deposited on the hot substrate surface. Control the spray time to 7min, and the FTO film can be obtained on the surface of the glass / quartz substrate.
[0084] The performance indicators of the obtained FTO film show the following characteristics: film thickness 651nm, square resistance value 6.8Ω / □, grain size controlled at 69nm, surface roughness RMS 5.5nm. After being placed at room temperature for 3 months, the square resistance change rate is 0.8%.
[0085] Example 4
[0086] A method for preparing a fluorine-doped tin oxide film by ultrasonic atomization, the specific steps are as follows:
[0087] ①Prepare the spraying liquid: Dissolve 92.50g of SnCl2·2H2O in 1000mL of industrial methanol, and add 23.47g of trifluoroacetic acid solution and 0.10g of LiOH thereto. Afterwards, place the obtained mixed solution in an autoclave for reaction. The reaction temperature is set to 66°C, the reaction pressure is 0.15MPa, and the reaction time is 1 hour. After the solution after the reaction is cooled to room temperature, take it out and dry it at 70°C to obtain a yellow-green powder. Dissolve these powders in 957mL of industrial ethanol to obtain a light yellow low-acid FTO spraying liquid. In this embodiment, the molar ratio of tin source: methanol: trifluoroacetic acid: lithium hydroxide: ethanol is 1:60.02:0.5:0.01:40.13.
[0088] ②Preparation of thin film: Place the cleaned glass / quartz substrate in the spray chamber at 46°. Then add a certain amount of FTO spray liquid into the ultrasonic sprayer. Subsequently, nitrogen with a purity of 99.99% is introduced into the coating chamber, and the gas flow rate is controlled at 6mL / min. The carrier gas introduced into the coating chamber is introduced into the bottom of the bottle of sodium chloride solution with a concentration of 5.4mol / L. The liquid column height is 20cm, and the gas pressure in the coating chamber is regulated; start the iodine tungsten lamp to radiate heat to the substrate. After 8s, the substrate temperature reaches 420℃ and maintains for 30s. Then turn on the ultrasonic atomization plate, and the cavitated spray liquid droplets are brought into the spray chamber by the carrier gas and deposited on the hot substrate surface. Control the spray time to 10min, and the FTO film can be obtained on the surface of the glass / quartz substrate.
[0089] The performance indicators of the obtained FTO film show the following characteristics: film thickness 786nm, square resistance value 5.4Ω / □, grain size controlled at 72nm, surface roughness RMS 6.0nm. After being placed at room temperature for 3 months, the square resistance change rate is 1.4%.
[0090] Example 5
[0091] A method for preparing a fluorine-doped tin oxide film by ultrasonic atomization, the specific steps are as follows:
[0092] ①Prepare the spraying liquid: 70.12g of SnCl4·5H2O and 24.82g of SnCl2·2H2O are mixed in 1000mL of industrial methanol, and 17.60g of trifluoroacetic acid solution and 0.07g of LiOH are added thereto. Afterwards, the obtained mixed solution is placed in a high pressure reactor for reaction. The reaction temperature is set to 69°C, the reaction pressure is 0.23MPa, and the reaction time is 1 hour. After the solution after the reaction is cooled to room temperature, it is taken out and dried at 70°C to obtain a yellow-green powder. Dissolve these powders in 987mL of industrial ethanol to obtain a light yellow low-acid FTO spraying liquid. In this embodiment, the molar ratio of tin source: methanol: trifluoroacetic acid: lithium hydroxide: ethanol is 1:90.86:0.57:0.01:62.66.
[0093] ②Preparation of thin film: Place the cleaned glass / quartz substrate in the spray chamber at 45°. Then add a certain amount of FTO spray liquid into the ultrasonic sprayer. Subsequently, nitrogen with a purity of 99.99% is introduced into the coating chamber, and the gas flow rate is controlled at 7mL / min. The carrier gas introduced into the coating chamber is introduced into the bottom of the bottle of sodium chloride solution with a concentration of 5.4mol / L. The liquid column height is 23cm, and the gas pressure in the coating chamber is regulated; start the iodine tungsten lamp to radiate heat to the substrate. After 7.9s, the substrate temperature reaches 410℃ and maintains for 30s. Then turn on the ultrasonic atomization plate, and bring the cavitated spray liquid droplets into the spray chamber by the carrier gas and deposit them on the hot substrate surface. Control the spray time to 8min, and you can get a FTO film on the surface of the glass / quartz substrate.
[0094] The performance indicators of the obtained FTO film show the following characteristics: film thickness 705nm, square resistance value 8.0Ω / □, grain size controlled at 70nm, surface roughness RMS 5.9nm. After being placed at room temperature for 3 months, the square resistance change rate is 1.5%.
[0095] The above-mentioned fluorine-doped tin oxide transparent conductive film spraying liquid includes the following components: tin source, alcohol, trifluoroacetic acid and lithium hydroxide. The pH of the spraying liquid is above 2.0, and the acidity is relatively low compared to the traditional one. It can avoid the problem that "the aqueous solution or organic solution prepared by SnCl4 and SnCl2 will generate a large amount of HCl due to nucleophilic substitution reaction during the preparation process, resulting in excessive acidity of the prepared solution, and the pH value is often below 1.0; the high acidity of the droplets will increase the microscopic defects of the prepared film layer, and the roughness of the film surface will increase, which will increase the amount of gas adsorbed by the film layer, and seriously affect the stability of the film resistance". It can improve the microscopic defects of the film layer, reduce the roughness of the film surface, reduce the amount of gas adsorbed by the film layer, and improve the stability of the film resistance. Moreover, the present application innovatively adopts a combination of trifluoroacetic acid and lithium hydroxide, which has the advantages of reduced and controllable acidity, controllable film thickness, and high fluorine doping level, which can better solve the corrosion problems of film growth and coating equipment, and provide conditions for the preparation of high-quality FTO films.
[0096] The present invention provides a method for preparing an FTO film with few microscopic defects, small specific surface area and low film making cost; based on the improvement of conventional ultrasonic spray equipment, the environment of film deposition is changed from open to closed, the substrate heating method is iodine tungsten lamp radiation heating, and a device with controllable aerosol pressure in the spray chamber is added to realize the control of key process parameters such as heating rate, aerosol pressure in the closed chamber and substrate temperature drop, so as to further achieve the following effects on the basis of conventional ultrasonic spray film making: ① rapid heating (heating rate up to 100°C / s), ② stable temperature field during film coating, and ③ controllable growth of the film layer. Through rapid heating, the attachment of impurity particles on the surface of the substrate and the diffusion of impurity elements of the substrate to the film are reduced, so as to achieve the purpose of reducing film defects; the closed space design reduces the influence of the substrate temperature on the spray droplets and airflow to the minimum, and at the same time, the accuracy of the combined temperature control meets the requirements of stable temperature field of film preparation, and effectively reduces the internal stress of the film layer; the tail pressure design of the spray chamber, in conjunction with the gas pressure regulation at the carrier gas source end, can effectively control a series of physical changes, thermal decomposition reactions and crystallization nucleation processes occurring during the flight of the droplets in the spray chamber, so as to achieve the purpose of controlling the growth of the film. At the same time, the present application adopts a new acidity control technology to obtain a FTO spray liquid with low acidity (pH value greater than 2.0) and high fluorine doping level, solves the corrosion problems of film growth and coating equipment, and provides conditions for the preparation of high-quality FTO films. The present invention can prepare an FTO film with few microscopic defects, small specific surface area, low film square resistance, and small static resistance change rate of the film layer. The film thickness is controlled at 600-800nm. There are no defects such as cracks, second-phase impurity particles, abnormal protrusions and pits on the surface and inside of the film. The film grains grow densely and uniformly, basically maintaining at 70±5nm. The surface of the FTO film is smooth and flat, with a small surface roughness (RMS of the surface root mean square roughness is 5.5-6.2nm, 5μm×5μm range), and the lowest square resistance can reach 4.4Ω / □. It can be used as a semiconductor electric heating film and applied to high-end products such as small infrared heating tubes and plates with low power consumption.
[0097] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. It should be noted that "in one embodiment", "for example", "for example", etc. in this application are intended to illustrate the present application, rather than to limit the present application. The above-described embodiments only express several implementation methods of the present application, and the description is relatively specific and detailed, but it cannot be understood as a limitation on the scope of the patent application. It should be pointed out that for a person of ordinary skill in the art, without departing from the concept of the present application, several variations and improvements can also be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be subject to the attached claims.
Claims
1. A fluorine-doped tin oxide transparent conductive film spraying liquid, characterized in that: The invention comprises the following components: a tin source, an alcohol, a fluorine-containing dopant and lithium hydroxide, wherein the pH value of the spraying liquid is above 2.
0.
2. The spraying liquid according to claim 1, characterized in that The tin source is at least one of SnCl4·5H2O or SnCl2·2H2O or SnCl4·5H2O and SnCl2·2H2O; And / or, the alcohol is at least one of methanol and ethanol; And / or, the fluorine-containing dopant is trifluoroacetic acid; and / or, the pH of the spraying liquid is above 3.0; And / or, the molar ratio of the tin source, the fluorine-containing dopant and the lithium hydroxide is 1: "0.45-0.85": "0.05-0.2".
3. The spraying liquid according to claim 2, characterized in that: The spraying liquid includes a tin source, methanol, trifluoroacetic acid, lithium hydroxide, and ethanol, wherein the mass volume ratio of the tin source, methanol, trifluoroacetic acid, lithium hydroxide, and ethanol is: 1 (g): 6-12 (ml): 0.1-0.3 (g): 0.0001-0.01 (g): 6-12 (ml); And / or, the molar ratio of tin source: methanol: trifluoroacetic acid: lithium hydroxide: ethanol is 1: "55-95": "0.45-0.85": "0.05-0.2": "30-70".
4. The spraying liquid according to claim 3, characterized in that: The preparation method of the spray liquid is as follows: a tin source is dissolved in methanol, and trifluoroacetic acid and lithium hydroxide are added, the obtained mixed solution is placed in a high-pressure reactor for reaction, the reaction temperature is set to 65-70°C, the reaction pressure is 0.1-0.3MPa, the reaction time is 1 hour, after the solution after the reaction is cooled to room temperature, it is taken out and dried at 70°C to obtain a yellow-green powder; the yellow-green powder is dissolved in ethanol to obtain the spray liquid.
5. A method for preparing a fluorine-doped tin oxide transparent conductive film by ultrasonic atomization, characterized in that: The fluorine-doped tin oxide transparent conductive film is prepared by ultrasonic atomization of the spraying liquid as described in any one of claims 1 to 4.
6. The method according to claim 5, characterized in that The method comprises the following steps: providing the spraying liquid; heating the substrate surface; The spraying liquid is ultrasonically atomized and sprayed and deposited on the surface of the substrate to prepare the fluorine-doped tin oxide transparent conductive film.
7. The method according to claim 6, characterized in that The substrate surface temperature is heated to 380-420°C.
8. The method according to claim 7, characterized in that The substrate is glass or quartz; and / or, using an iodine tungsten lamp to radiate and heat the surface of the substrate; and / or, when the spraying liquid is ultrasonically atomized and spray-deposited on the surface of the substrate, the deposition environment is closed; And / or, when the substrate is spray-deposited, the substrate is placed at an inclination angle ranging from 40° to 50°, the carrier gas is 99.99% pure nitrogen, and the carrier gas flow rate is controlled at 6 to 8 mL / min; the liquid at the bottom of the bottle in the spray chamber is a saturated sodium chloride solution, and the liquid column height is maintained at 20 to 25 cm.
9. The method according to claim 6, characterized in that The spraying ultrasonic atomization has a mist output of 4800±500mL / h and a thin film deposition time of 5 to 10min; And / or, the thickness of the fluorine-doped tin oxide transparent conductive film is 600-800 nm; And / or, the square resistance of the fluorine-doped tin oxide transparent conductive film is 4.4-8.0Ω / □; And / or, the grain size of the fluorine-doped tin oxide transparent conductive film is 70±5 nm; And / or, the surface roughness RMS of the fluorine-doped tin oxide transparent conductive film is 5.5-6.2 nm.
10. An infrared heating device, characterized in that: The invention comprises a substrate and a fluorine-doped tin oxide transparent conductive film prepared on the surface of the substrate, wherein the fluorine-doped tin oxide transparent conductive film is prepared by the method as described in any one of claims 5 to 9.
Citation Information
Cited By
High-valence multi-element co-doped tin oxide transparent conductive film and preparation method thereof
CN121641551A
